2014
DOI: 10.1155/2014/141747
|View full text |Cite
|
Sign up to set email alerts
|

Two Faces of TGF-Beta1 in Breast Cancer

Abstract: Breast cancer (BC) is potentially life-threatening malignancy that still causes high mortality among women. Scientific research in this field is focused on deeper understanding of pathogenesis and progressing of BC, in order to develop relevant diagnosis and improve therapeutic treatment. Multifunctional cytokine TGF-β1 is one of many factors that have a direct influence on BC pathophysiology. Expression of TGF-β1, induction of canonical and noncanonical signaling pathways, and mutations in genes encoding TGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
146
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(159 citation statements)
references
References 137 publications
(363 reference statements)
6
146
0
6
Order By: Relevance
“…The TGF-β pathway has a dual role in both tumor suppression and tumor promotion (Sheen et al, 2013). Zarzynska reported that in the early stages of breast cancer, TGF-β inhibited epithelial cell cycle progression and promoted apoptosis to suppress tumorigenesis (Zarzynska, 2014). Therefore, we suggest that PR might suppress tumorigenesis in DMBA-induced breast tumor rats by increasing TGF-β expression.…”
Section: Journal Of Agricultural Sciencementioning
confidence: 81%
“…The TGF-β pathway has a dual role in both tumor suppression and tumor promotion (Sheen et al, 2013). Zarzynska reported that in the early stages of breast cancer, TGF-β inhibited epithelial cell cycle progression and promoted apoptosis to suppress tumorigenesis (Zarzynska, 2014). Therefore, we suggest that PR might suppress tumorigenesis in DMBA-induced breast tumor rats by increasing TGF-β expression.…”
Section: Journal Of Agricultural Sciencementioning
confidence: 81%
“…The disparate action on DNA synthesis and nestin expression suggested that upregulation of the intermediate filament protein was insufficient to promote entry into the cell cycle in response to TGF-␤ 1 . Thus one or more of the myriad signaling events recruited by TGF-␤ 1 may have suppressed a downstream target of nestin required for DNA synthesis (41). Nonetheless, the in vitro data suggest that nestin upregulation in the vasculature of suprarenal abdominal aorta-constricted rats may have occurred in part via ANG II acting directly and/or in a concerted fashion via the synthesis and release of EGF and TGF-␤ 1 .…”
Section: Discussionmentioning
confidence: 97%
“…TGFb that acts as a tumor suppressor at early stages of cancer has also been shown to promote malignant properties of tumors, including invasion and metastasis at the later stages. It is found enriched in breast cancer bone metastasis (11). p53, on the other hand, has been shown to repress EMT by transcriptional repression of SNAIL and noncoding regulation mediated by miRNAs (12).…”
Section: Introductionmentioning
confidence: 99%